2004
DOI: 10.1093/geronb/59.6.p305
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Performance by Older Persons on a Simulated Telecommuting Task

Abstract: Telecommuting work represents a strategy for managing the growing number of older people in the workforce. This study involved a simulated customer service telecommuting task that used e-mail to answer customer queries about media-related products and company policies. Participants included 27 "younger" older adults (50-65 years) and 25 "older" older adults (66-80 years). The participants performed the task for two 2-hr sessions a day over 4 consecutive days. Although both age groups showed significant improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Processing speed, memory, attention Sharit, Czaja, Nair, and Lee [54] Interactive telephone voice menu systems Working memory Sharit, Czaja, Hernandez, Yang, Perdomo, Lewis, Lee and Nair [53] Information search and retrieval/e-mail Psychomotor speed, working memory, verbal abilities, attention Pak, Rogers, and Fisk [41] Computer-based information search…”
Section: Overview Of Aging and Cognitionmentioning
confidence: 99%
“…Processing speed, memory, attention Sharit, Czaja, Nair, and Lee [54] Interactive telephone voice menu systems Working memory Sharit, Czaja, Hernandez, Yang, Perdomo, Lewis, Lee and Nair [53] Information search and retrieval/e-mail Psychomotor speed, working memory, verbal abilities, attention Pak, Rogers, and Fisk [41] Computer-based information search…”
Section: Overview Of Aging and Cognitionmentioning
confidence: 99%
“…In a previous study evaluating an e-mail-based customer service task (Sharit et al, 2004), we found age differences in task performance such that the younger participants (aged 50-65 years) performed better than the older participants (aged 66-80 years). However, the results overall demonstrated performance improvements for both age groups with practice.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 77%
“…This view is largely consistent with investment theory (Horn & Cattell, 1967), which postulates that higher levels of fluid and crystallized intelligence enable an individual to learn new knowledge and skills. Although researchers originally postulated this theory to explain learning in children, scientists can apply it to situations involving skill acquisition with older adult populations, given that skill acquisition represents a dynamic process between acquired cognitive abilities and the learning of new material.In a previous study evaluating an e-mail-based customer service task (Sharit et al, 2004), we found age differences in task performance such that the younger participants (aged 50-65 years) performed better than the older participants (aged 66-80 years). However, the results overall demonstrated performance improvements for both age groups with practice.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Future adaptations of technology and telecommuting hold challenges and potential solutions for remedying some of the sensory and everyday needs of older adults (Patrickson, 2002;Pew & Van Hemel, 2004;Sharit et al, 2004).…”
Section: A Sensory Changesmentioning
confidence: 99%